Numerical analysis on the anode active thickness using quasi-three-dimensional solid oxide fuel cell model - Tan, Wee Choon; Eng Aik Lim, Eng Aik Lim; Abd Rahman, Hamimah; Abdul Samat, Abdullah; Cheen Sean Oon, Cheen Sean Oon (Elsevier, 2023)
A quasi-three-dimensional solid oxide fuel cell (SOFC) model reduces the computational cost by strategically ignoring the thinnest direction in an SOFC by incorporating a chargetransfer current density model to represent its active thickness in electrodes to represent its complex phenomenon in an electrode. Therefore, high accuracy of this charge-transfer current density model is required. The concentration loss is mathematically related to the charge-transfer current density based on the dusty-gas model together with activation and ohmic losses in this work. The numerical results from this study are validated with the experimental results. The influence of anode's thickness towards anode active thickness is studied with the anode thickness of 5, 10, 50, 100, 500 and 1000 mm. It is found that the quasi-three-dimensional SOFC model is capable of analysing SOFC with a sufficiently thick electrode. Also, a thick electrode and a high average current density result in a thin active thickness.